Implementasi Program Tahfidzul Qur’anboarding School dalam Pembetukan Karakter Religius Peserta Didik di SMP-Qu Cahaya Al-Qur’an Padang Panjang - Tasman Firdaus; Romi Yilhas (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The occurrence of a multi-dimensional crisis, the mentality of the nation's children is bad, the decline in dignity is one of the importance of religious character education. To internalize the values of religious character to students, it is necessary to optimize education, one of which is character building through tahfidzul qur'an. character according to the Qur'an. This study aims to describe the program, methods and characters born from the tahfidz program. This research was conducted with a qualitative approach, while the data collection techniques used were the results of observations, interviews and documentation. Several results were obtained related to several Tahfidz programs implemented, namely daily, weekly, mid-semester and semester programs. Then the Qur'an Intensive (IQ) and at the end of the semester a Tasmi 'Akbar was held. Finally, the Mukhayyam Al-Qur'an program is held for two days after students return from school holidays with the aim of reviving children's memorization. To facilitate the memorization of the Qur'an, various methods were applied, namely: the Tiqrar, Talaqqi, Tasmi 'Tsuna'i, and Rabath methods. The religious characters that are implemented from tahfidzu that can be seen are honest, disciplined, patient, diligent, spontaneous without being asked, independent, and istiqomah in carrying out religious orders. The conclusion is that memorizing the Qur'an with a good and measurable program, then using the right method, will be able to shape the religious character of the students or the perpetrators.